ANALISIS SHOPPING LIFESTYLE, STORE ATMOSPHERE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA METEOR KAMPUNG DISTRO KEDIRI - Meythasari, Fifi; Samari, Samari; Leksono, Poniran Yudho (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the effect of shopping lifestyle, store atmosphere, and product quality partially or simultaneously on purchasing decisions at Meteor Kampung Distro Kediri. This study uses causality quantitative research methods. The population in this study were consumers who had bought Meteor Kampung Distro Kediri products. The sampling method used nonprobability sampling which determined a sample of 40 respondents. Data collection in this study using observation, interviews, and distributing questionnaires. Data analysis in this study uses a validity test, reliability test, classical assumption test, multiple linear regression analysis, and coefficient of determination ( ), t-test, and f test. The results of the t-test data analysis state that shopping lifestyle and product quality partially affect purchasing decisions at Meteor Kampong Distro Kediri, while store atmosphere has no partial effect on purchasing decisions at Meteor Kampong Distro Kediri. Furthermore, the results of the f-test data analysis state that shopping lifestyle, store atmosphere, and product quality simultaneously influence purchasing decisions at Meteor Kampung Distro Kediri.